2017
DOI: 10.18632/oncotarget.16483
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic scores based on the preoperative plasma fibrinogen and serum albumin level as a prognostic factor in patients with upper urinary tract urothelial carcinoma

Abstract: This study is to clarify the prognostic value of preoperative plasma fibrinogen and serum albumin level, as known as FA score, in a cohort of Chinese patients with upper urinary tract urothelial carcinoma (UTUC). We retrospectively evaluated clinicopathological data on 169 patients who underwent surgery between 2006 and 2013. The FA score was calculated based on cutoff values of 3.53g/L for fibrinogen and 43.56 g/L for albumin. Overall survival and cancer specific survival was assessed using the Kaplan-Meier m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
(45 reference statements)
3
13
0
Order By: Relevance
“…The FA score, which is based on preoperative fibrinogen and albumin, was developed as a scoring system to reflect inflammation and the nutrition status by Matsuda and has been recognized as a novel clinical prognostic biomarker in several cancers, showing superior predictive power in esophageal cancer patients. 19 , 20 Consistent with these findings, our results indicate that the FA score is an independent prognostic biomarker of PFS and OS in skull base chordoma patients. The FA score may be a valuable clinical score for the assessment of survival due to its relatively low cost and easy accessibility in daily practice.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The FA score, which is based on preoperative fibrinogen and albumin, was developed as a scoring system to reflect inflammation and the nutrition status by Matsuda and has been recognized as a novel clinical prognostic biomarker in several cancers, showing superior predictive power in esophageal cancer patients. 19 , 20 Consistent with these findings, our results indicate that the FA score is an independent prognostic biomarker of PFS and OS in skull base chordoma patients. The FA score may be a valuable clinical score for the assessment of survival due to its relatively low cost and easy accessibility in daily practice.…”
Section: Discussionsupporting
confidence: 86%
“… 17 , 18 Furthermore, considering the prognostic role of fibrinogen and albumin, the FA score, which is a novel scoring system that combines fibrinogen and albumin, has recently been reported, and this score can independently predict outcomes in patients with esophageal cancer and urothelial carcinoma. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…In addition to our analysis, recent studies also indicated a positive correlation between elevated plasma fibrinogen levels and poorer prognosis in other solid tumors including esophageal carcinoma, 37 39 small cell lung carcinoma, 40 non-small cell lung carcinoma, 41 upper urinary tract urothelial carcinoma, 42 , 43 epithelial ovarian cancer, 44 colorectal cancer, 45 renal cell carcinoma, 46 , 47 and gastric cancer. 48 , 49 There are several theories that may explain this association: 1) tumor progression is usually coupled with elevated inflammatory responses and leukocyte infiltration into tumor stroma.…”
Section: Discussionsupporting
confidence: 65%
“…Hypoproteinemia is indicative of systemic inflammatory response, and ALB level is a well-known biomarker for malnutrition. 24 Low PAB levels also indicate depletion of protein resulting from LG chronic inflammation. 40 …”
Section: Discussionmentioning
confidence: 99%